A comparative study of negative suction drainage in inguinal hernia operations at Saraswathi Institute of Medical Sciences, Pilkhua, Hapur Uttar Pradesh - Singh, Desh Pal; Goel, Saurabh; Kumar, Surendra (International Surgery Journal, 2021)
Background: The inguinal area is the weakest region of the abdominal wall. So, this is the most common site for the development of hernias. Inguinal hernias are the commonest amongst all the hernias and hernia repair is the most frequently done operation worldwide. There is no agreement among surgeons regarding the need for drains. Some use sparingly and some use it routinely. This study aims to evaluate the use of negative suction drain in inguinal hernia surgery. Methods: We studied sixty patients of inguinal hernias both direct and indirect for one year and followed up for next 1-2 years. This prospective study aimed to see the effect of negative suction drainage in hernia surgery. Results: Both the groups did well postoperatively. It was beneficial to put a negative suction drain in those patients who had a bigger hernia, fatty patients with the thick fatty lower abdominal wall and older patients. Conclusion: It is advisable to put a negative suction drain in inguinal hernia surgery and strongly advocated if the dissection had been difficult, old patients and fatty lower abdominal wall